Values and construction waste recycling: an application of the cognitive hierarchy to construction management education - Nobe, MaryEllen C., author; Cobb, R. Brian, advisor; Folkestad, James E., committee member; Dunbar, Brian H., committee member; Timpson, William M., committee member; Vaske, Jerry J., committee member (Colorado State University. Libraries, 2007)
Since it first emerged in the early 1990's, the green building movement has grown both in its acceptance and applications, but has yet to achieve widespread market penetration. Although there are a variety of reasons for this, including social, economic and political barriers; construction managers' lack of acceptance of green building has been identified as a major impediment. Construction management (CM) programs have sought to increase CM students' acceptance of green building, however, almost nothing is known about CM students' values and how they influence their environmental behaviors. Cognitive theory provides a framework in the form of the cognitive hierarchy that has potential for addressing this problem. This theory predicts behavior intentions as a function of values, value orientation, attitudes, and norms. The purpose of this study was to provide insights into how CM students' values influenced their environmental behavior intentions. The present study incorporated the cognitive hierarchy as a framework to examine the relationships between values and other cognitive determinants of behavior intention. This study also sought to confirm the full cognitive hierarchy model, including the role of values, using data from a single survey. In an attempt to examine the role of values along with other cognitive functions (environmental value orientation, attitude, and subjective norm) in determining behavior intention, this study had the following objectives: (a) to determine the direct relationship between values and each of the other components of the cognitive hierarchy, (b) to determine the direct relationships between components of the cognitive hierarchy and behavior intention, and (c) to determine the mediation role of value orientation, attitude, and subjective norm on direct relationships identified in parts a and b above. Findings of the present study have implications for both construction management education and social psychology research on cognitive determinates of environmental behavior.
Keywords: higher education; vocational education